AN ANALYSIS OF THE COHESION AND COHERENCE OF STUDENTS` ENGLISH WRITINGS AT THE SECOND GRADE OF SMAN 1 LABUAPI WEST LOMBOK - ., AYUB; K, SEKEN,; W, SUARNAJAYA, (Jurnal Pendidikan Bahasa Inggris, 2013)
Abstract This study aimed at analyzing students` writings in terms of: (1) the types of cohesive devices used; (2) the types of topical progressions; and (3) the problems of coherence. The subjects investigated were 30 second grade students of SMAN 1 Labuapi. There were two kinds of data collected: written and verbal data. In collecting the data, the students were given a writing task and the students and the English teacher were interviewed. The data were analyzed qualitatively based on Halliday and Hasans` theory of cohesion (1976) and Topical Progression Analysis of Lautamatti (1978) in Hoenisch (2009) and Almaden (2006). The results of study were (1) the students used the five types of cohesive devices to serve the coherence of their writings of which reference 40.84% with personal reference as the dominant use. Lexical cohesion was used 37.99% dominated with repetition. Then, it was followed by conjunction 19.60 %, ellipsis 1.35%, and substitution 0.29%; (2) the topical progression used was parallel progression with the percentage 56.84%, sequential progression 24.19%, and extended parallel progression 18.25%; (3) some problems in coherence of students` writings were reference, conjunction, lexical cohesion, tenses, auxiliary `to be`, passive voice, infinitive, gerund, subject-verb agreement, noun, preposition, and text structure. The result of the study indicates that cohesion and coherence have to be the emphasis in teaching writing and the English teachers have to be competent in evaluating the coherence of students` writings by applying TSA. Keywords: cohesive devices, topical progression, cohesion, coherence.